The Role of Company Performance in Determine Effect of ESGD on Risk of Financial Distress - Dian Oktarina (Jurnal Riset Akuntansi dan Keuangan, 2024)
This study aims to determine the role of company performance in assessing the effect of ESGD on the occurrence of financial distress. This study uses the dependent variable financial distress as measured by the Altman z-score method, the independent variable ESGD, whose score is obtained from the website of the BGK Foundation, and the intervening variable of company performance as measured by stock price. The samples used in this study are all non-financial and banking companies listed on the IDX in 2018-2021 and reporting the value of ESG disclosure on the BGK Foundation website. The tool used in this research is path analysis. The result of this study indicates that company performance and ESG disclosure have no effect on financial distress. ESG disclosure has a negative impact on company performance. In addition, company performance also cannot mediate the effect of ESGD on financial distress.